FENOMENA KURVA J PADA NERACA PERDAGANGAN INDONESIA DENGAN ENAM NEGARA MITRA DAGANG UTAMA - hapsari, anggraeni tri; Kurnia, Akhmad Syakir (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2018)
Whether a J curve phenomenon exists or not on the balance of trade has been an interest for empirical investigation in international economics. The phenomenon is typically associated with the response of the balance of trade to the exchange rate dynamics. Since a country has different trade features with different trading partners, the trade balances adjustment to the exchange rate dynamics should be seen as a head to head phenomenon. This paper investigates the effect of real effective exchange rate (REER) on the bilateral trade balance between Indonesia and its six major trading partners, namely Japan, China, Singapore, United States, South Korea and India on a quarterly basis over the period 1995.1 to 2013.4. The short run and the long run effect of the REER on the balance of trade is expected to be captured using error correction model (ECM) and vector error correction model (VECM). Subsequently, impulse response function is used to trace out the behavior of the bilateral trade balance in response to the REER shock whereas forecast error variance decomposition (FEVD) is used to decay the effect of innovation variables in the system. The result indicates that in the long run a J curve phenomenon appears on the bilateral trade balance between Indonesia and Japan, China, Singapore as well as South Korea. In the short run, a J curve phenomenon is seen on the bilateral trade balance between Indonesia and China as well as Singapore. This confirms that a J curve is a head to head phenomenon that has correlation with the trade features. Thus, the correction mechanism to the trade balance in response to the exchange rate shock (i.e. exchange rate market intervention) should count trade features as a consideration